Facial Dysmorphisms, Macrodontia, Focal Epilepsy, and Thinning of the Corpus Callosum: A Rare Mild Form of Kabuki Syndrome - Bruni, Valentina; Scozzafava, Cristina; Gnazzo, Maria; Parisi, Francesca; Sestito, Simona; Pensabene, Licia; Novelli, Antonio; Concolino, Daniela (Journal of Pediatric Genetics, 2020)
Kabuki syndrome (KS) is a rare genetic condition with multiple congenital abnormalities and developmental delay. The cardinal manifestations of KS include characteristic facial features, intellectual disability, skeletal defects, dermatoglyphic abnormalities, and postnatal growth deficiencies. Cardiac and urological malformations are commonly present in patient with KS, as well as language deficits and immunological abnormalities. Here, we reported a case of a child with an atypical form of KS, associated with macrodontia, corpus callosum dysmorphism, focal epilepsy responsive to antiepileptic treatment, and a novel KMT2D gene missense variant, c.2413C > T, never reported to date.
Keywords: Kabuki syndrome; KMT2D gene; focal epilepsy